2021
DOI: 10.1152/ajpcell.00548.2020
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation inward rectifier potassium channel modulators: discovery and molecular pharmacology

Abstract: Inward rectifying potassium (Kir) channels play important roles in both excitable and non-excitable cells of various organ systems and could represent valuable new drug targets for cardiovascular, metabolic, immune and neurological diseases. In non-excitable epithelial cells of the kidney tubule, for example, Kir1.1 (KCNJ1) and Kir4.1 (KCNJ10) are linked to sodium reabsorption in the thick ascending limb of Henle's loop and distal convoluted tubule, respectively, and have been explored as novel-mechanism diure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 157 publications
1
19
0
Order By: Relevance
“…Our study highlights the GIRK channels as potentially important players in GNB1 Encephalopathy. Previous studies demonstrated strong links between malfunction or altered expression of neuronal GIRKs and epilepsy ( Jeremic et al., 2021 ; Luján et al., 2014 ; Lüscher and Slesinger, 2010 ) and GIRK openers have been found beneficial in treating several types of epilepsy in animal models ( Huang et al., 2018 ; Weaver and Denton, 2021 ; Wydeven et al., 2014 ; Zhao et al., 2020 ). Accordingly, the use of GIRK-directed therapies should be considered for treating the epileptic symptoms in GNB1 Encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights the GIRK channels as potentially important players in GNB1 Encephalopathy. Previous studies demonstrated strong links between malfunction or altered expression of neuronal GIRKs and epilepsy ( Jeremic et al., 2021 ; Luján et al., 2014 ; Lüscher and Slesinger, 2010 ) and GIRK openers have been found beneficial in treating several types of epilepsy in animal models ( Huang et al., 2018 ; Weaver and Denton, 2021 ; Wydeven et al., 2014 ; Zhao et al., 2020 ). Accordingly, the use of GIRK-directed therapies should be considered for treating the epileptic symptoms in GNB1 Encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether the ROMK protein acts as a possible mitoK ATP channel-forming component, research has focused on the use of compounds regulating the activity of this protein. For example, it was reported that VU591 inhibits ROMK channels with high specificity [ 62 , 63 , 64 ]. However, this molecule induced mitochondrial depolarization and matrix contraction in mitochondria from both wild-type and ROMK knockout cells.…”
Section: Modulators Of Mitochondrial Atp-sensitive Potassium Channelsmentioning
confidence: 99%
“…Currently, the activation of neuronal GIRK channels, specifically GIRK1/2, is considered a promising pharmaceutical strategy against many neurological and psychiatric conditions, such as epilepsy, hyperalgesia, and neurodegenerative diseases [1,3,5,6]. In this article, we report the identification of AsKC11, a Kunitz toxin/peptide found in Anemonia sulcata, that activates GIRK channels.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, several studies have shown the functions of GIRK channels in pathological conditions. Pharmacologically increasing the activity of GIRK channels can induce efficacy in rodent models of numerous neurological or psychiatric disorders, for instance, antiseizure, anxiolytic, antinociceptive, and rescue of amyloid-βevoked deficits in hippocampal function [2,3,[11][12][13][14][15][16][17][18]. These studies suggest the therapeutic potential of activating neuronal GIRK channels, especially the primary GIRK1/2, to treat brain diseases in humans [5].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation